Réponses

2013-11-02T09:30:05+01:00
I = (x+1)(x+5)
   x²+5x+x+5=x²+6x+5
J = (4x+5)(2x+6)
   8x²+24x+10x+30=8x²+34x+30
K = (5u+1)(2-3u)
     10u-15u²+2-3u=-15u²+7u+2
L = (-3+n)(-2n-5)
   6n+15-2n²-5n=-2n²+n+15
M = 6+(5y-2)(3-4y)
     6+15y-20y²-6+8y=-20y²+23y
N = 5z-(4z+3)(-2z-5)
     5z-(-8z²-20z-6z-15)
     5z-8z²+20z+6z+15=-8z²+31z+15
je trouve exactement comme toi
merci à vous :)
2013-11-02T10:14:14+01:00
I = ( x + 1 ) ( x + 5 )  
=  x * x + x * 5 + 1 * x + 1 * 5
= x^2 + 5x + 1x + 5
= x^2 + 6x + 5

J = ( 4x + 5 ) ( 2x + 6 )
= 4x * 2x + 4x * 6 + 5 * 2x + 5 * 6
= 8x^2 + 24x + 10x + 30
= 8x^2 + 34x + 30

K = ( 5u + 1 ) ( 2 - 3u )
= 5u * 2 + 5u * (-3u) + 1 * 2 + 1 * (-3u)
= 10u - 15u^2 + 2 - 3u
= 7u - 15u^2 + 2

L = ( -3 + n ) ( -2n - 5 )
= -3 * (-2n) - 3 * (-5) + n * (-2n) + n * (-5)
= -6n + 15 - 2n^2 - 5n
= -11n + 15 - 2n^2

M = 6 + ( 5y - 2 ) ( 3 - 4y )
= 6 + 5y * 3 + 5y * (-4y) - 2 * 3 - 2 * (-4y)
= 6 + 15y - 20y^2 - 6 + 8y
= 23y - 20y^2

N = 5z - ( 4z + 3 ) ( -2z - 5 )
= 5z - 4z * (-2z) + 4z * (-5) + 3 * (-2z) + 3 * (-5)
= 5z + 8z^2 - 20z - 6z - 15
= -21z + 8z^2 - 15